Studi Konstruksi Sosial Perkosaan pada Kelompok Pelaku Berusia di Bawah 18 Tahun - Emi Kosvianti; Agung Suhadi; Nopia Wati; Riska Yanuarti; Bintang Agustina Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explain the construction of rape among underage perpetrators (14 to 17 years). The design of this research is qualitative with a phenomenological approach. The results of the study found that boys who were involved in rape cases could interpret rape in 3 forms, namely: as forced sex, consensual sex and deviant solidarity in boys' friendship groups. Overall, the construction they built illustrates the strong existence of patriarchal culture in rape cases involving perpetrators under 18 years of age. This is reflected in the form of domination, oppression, and victim blaming. In conclusion, the role of patriarchal culture in rape and injustice against women. Keywords: Social Construction, Patriarchy, Child Perpetrators, Rape